Development of small innovative entrepreneurship and its effectiveness in the national economy of the Republic of Kazakhstan - Amankeldi, A.A.; Saubetovа, B.S.; Nigmetovа, G.Zh.; Akhmetova, G.T.; Myrzhykbayeva, A.B. (BUKETOV BUSINESS REVIEW, 2024)
Object: The development of small innovative entrepreneurship contributes to the achievement of important social and economic goals. In this context, a number of important indicators can be used to evaluate the development of small business. These indicators include the number of small businesses operating in the small sector of the economy, the average wage rate, the growth of small business production, and the growth of investments in the small business sector. It helps to assess the effectiveness of investments in the small business sector. In the current economic literature, the term “innovation” can be used to emphasize relevant and widely used concepts. It is important because it shows the processes of creating new paradigms of economic development through innovation and science education. Small innovative entrepreneurship plays an important role in the creation of innovative infrastructure and contributes to the integration of scientific production into the economy through the transfer of scientific knowledge and technologies. Currently, it's evident that the financial health of Kazakhstan is closely linked to harnessing the economic capabilities of small-scale enterprises, along with the opportunities and provisions for their financial backing, highlighting the critical role of small businesses in the country's economic progression. Methods: For an article on the development of small innovative entrepreneurship in Kazakhstan and its effectiveness in the national economy, it is proposed to use an integrated methodological approach. First, review existing research and literature to assess the current status and dynamics of the sector, and analyze statistical data to understand its scope and contribution to the country's economy. Based on the data obtained, it will be possible to formulate targeted recommendations to improve the situation in the field of small innovative entrepreneurship, thereby contributing to the sustainable economic development of the country. Findings: The study highlights the significant contribution of small innovative entrepreneurship to the economic development of Kazakhstan, highlighting its role in creating jobs and stimulating innovation. Yet, for small enterprises to reach their full potential, enhancing governmental assistance and eliminating present obstacles is essential. This will facilitate the better incorporation of small businesses into the broader national economy. Conclusions: The article explores the impact of small innovative entrepreneurship on the economy of Kazakhstan, analyzing government support measures and their effectiveness. The focus is on identifying barriers to growth and proposing strategies to enhance the contribution of small businesses to national economic development.